The profile and contribution of rare germline copy number variants to cancer risk in Li-Fraumeni patients negative for TP53 mutations - Amanda G Silva; Ana Cristina Victorino Krepischi; P. Pearson; Pierre Hainaut; Carla Rosenberg; Maria Isabel Achatz (2014)
The Li-Fraumeni syndrome (LFS) is an inherited rare cancer predisposition syndrome characterized by a variety of early-onset tumors. Although germline mutations in the tumor suppressor gene TP53 account for over 50% of the families matching LFS criteria, the lack of TP53 mutation in a significant proportion of LFS families, suggests that other types of inherited alterations must contribute to their cancer susceptibility. Recently, increases in copy number variation (CNV) have been reported in LFS individuals, and are also postulated to contribute to LFS phenotypic variability. Seventy probands from families fulfilling clinical criteria for either Li-Fraumeni or Li-Fraumeni-like (LFS/LFL) syndromes and negative for TP53 mutations were screened for germline CNVs. We found a significantly increased number of rare CNVs, which were smaller in size and presented higher gene density compared to the control group. These data were similar to the findings we reported previously on a cohort of patients with germline TP53 mutations, showing that LFS/LFL patients, regardless of their TP53 status, also share similar CNV profiles. These results, in conjunction with our previous analyses, suggest that both TP53-negative and positive LFS/LFL patients present a broad spectrum of germline genetic alterations affecting multiple loci, and that the genetic basis of LFS/LFL predisposition or penetrance in many cases might reside in germline transmission of CNVs.